Religion and modern political process (Journal of Philosophy Culture and Political Science, 2018)
In this article the influence of religion on the political processes in modern society. In world society, the religion makes a very important function, saving the national cultural values, presenting as one of the key elements of national identity. It should be noted that religion has a profound and powerful influence on all aspects of the political process. Identified trends and new forms of interaction between religion and the political process in modern conditions. Particular importance is given to the way in modern conditions is realized interreligious dialogue as increased religiosity affects the stability and security of States. Examined the factors affecting the relationship between religion and politics , as well as the role of religion in the political process , in different spheres of society. The article concludes that today the religious factor in world politics, largely due to ongoing globalization processes in the world, has ever-increasing value that manifests itself in various forms, but by analyzing the influence of religion and the church on the political processes in the world , it is necessary to take into account the particularities of religious heterogeneity of the international community. Key words: political process, religion, politics, politization of the religion, globalization